Prognostic value of elevated lipoprotein(a) in patients with acute coronary syndromes. (7th May 2019) - Gencer, Baris; Rigamonti, Fabio; Nanchen, David; Vuilleumier, Nicolas; Kern, Ilse; Aghlmandi, Soheila; Klingenberg, Roland; Räber, Lorenz; Auer, Reto; Carballo, David; Carballo, Sebastian; Heg, Dik; et al.
Abstract: Background: Minimal lipoprotein(a) [Lp(a)] target values are advocated for high‐risk cardiovascular patients. We investigated the prognostic value of Lp(a) in the acute setting of patients with acute coronary syndromes (ACS). Materials and methods: Plasma levels of Lp(a) were collected at time of angiography from 1711 patients hospitalized for ACS in a multicentre Swiss prospective cohort. Associations between elevated Lp(a) ≥30 mg/dL (cut‐off corresponding to the 75th percentile of the assay) or Lp(a) tertiles at baseline, and major adverse cardiovascular events (MACE) at 1 year, defined as a composite of cardiac death, myocardial infarction or stroke, were assessed using hazard ratios (HR) and 95% confidence intervals (CI) adjusting for traditional cardiovascular risk factors (age, sex, smoking, diabetes, hypertension, low‐density lipoprotein cholesterol [LDL‐C], high‐density lipoprotein cholesterol [HDL‐C] and triglycerides. Results: Lp(a) levels range between 2.5 and 132 mg/dL with a median value of 6 mg/dL and a mean value of 14.2 mg/dL. A total of 276 patients (23.0%) had Lp(a) plasma levels ≥30 mg/dL. Patients with elevated Lp(a) were more likely to be of female gender and to have higher levels of total cholesterol, LDL‐C, HDL‐C and triglycerides. Higher Lp(a) was associated with failure to reach the LDL‐C target <1.8 mmol/L at 1 year (HR 1.71, 95% CI 1.13‐2.58, P = 0.01). No association was found between elevated Lp(a) and MACE at 1 year (HR 1.05, 95% CI 0.64‐1.73), nor for Lp(a) tertiles (HR 0.82, 95% CI 0.52‐1.28, P > 0.20) or standardized continuous variables (0.98, 95% CI 0.82‐1.19 for each increase of standard deviation). Conclusions: Our real‐world data suggest high Lp(a) levels at time of angiography are not predictive for cardiovascular outcomes in patients otherwise medically well controlled, but might be useful to identify patients who would not be on LDL‐C targets 1 year after ACS.